IoT enabled soil moisture sensor based irrigation in banana - Ravi, I.; G. Prabhu; Shelake, P. S.; Selvarajan, R.; Patel, V. B. (Indian Horticulture, 2025)
Bananas are a crucial staple crop worldwide, with India leading in globalproduction but contributing only a small fraction to international exports due to a focus on domestic demand. Climate change poses significant challenges to banana cultivation, including increased storm frequency, drought, and temperature extremes, necessitating adaptive measures for sustainable production. This study explores the role of Internet of Things (IoT) technology in improving water and nutrient use efficiency in banana farming through automated, sensor-based smart irrigation systems. IoT-enabled moisture sensors were tested in a field experiment at ICAR-National Research Centre for Banana to automate irrigation in response to real-time soil moisture data, optimizing resource usage. Results showed a 25-30% reduction in water usage and a 15-20% decrease in nutrient application without compromising yield. The IoT system increased crop productivity, reduced operational costs, and enhanced nutrient uptake. While IoT-based smart irrigation demonstrates substantial potential, widespread adoption will require addressing challenges related to cost, rural infrastructure, data management, and user training. Future opportunities include scaling IoT solutions, developing cost-effective systems, and refining technology to adapt to diverse soil types and farming contexts. Implementing AI and ML in horticulture through IoT can supportsustainable, efficient, and resilient banana cultivation in India, contributing to enhanced food security and resource conservation.